(untitled) (Third Sector Social Economic Review, 2022)
The purpose of this study is to examine the mediating role of organizational commitment in the relationship between high involvement human resources practices and organizational citizenship behavior. The data of the research were obtained from a total of 209 participants working in various industries in Turkey using the survey technique. The construct validity of the research was ensured by performing explanatory and confirmatory factor analysis. Correlation and linear regression analyzes were performed to test the predicted relationships. The results showed that the recognition dimension has a positive and significant relationship with organizational citizenship behavior, and organizational commitment has a partial mediation effect in this relationship. Moreover, it was found that the relationship between information-sharing, fair rewards and empowerment, which is among the high involvement human resources practices, and organizational citizenship behavior is positive but not significant. This study indicated that the recognition dimension will increase organizational citizenship behaviors in organizations and that organizational commitment has a mediating effect in this relationship.